Djerba 1994, souvenirs de mission - Adler, Israel (Yuval, 1994)
Keywords: Judaïsme – Djerba

Djerba (doc 7) - Adler, Israel (1994)
‎1 cassette Digital Audio Tape : digital. stéréo ; ‎3 ‎7/‎8 x ‎2 ‎1/‎2 in., ‎1/‎8 in. tape
Keywords: Judaïsme – Djerba

Djerba (doc 6) - Adler, Israel (1994)
‎1 cassette Digital Audio Tape : digital. stéréo ; ‎3 ‎7/‎8 x ‎2 ‎1/‎2 in., ‎1/‎8 in. tape
Keywords: Judaïsme – Djerba

Djerba (doc 5) - Adler, Israel (1994)
‎1 cassette Digital Audio Tape : digital. stéréo ; ‎3 ‎7/‎8 x ‎2 ‎1/‎2 in., ‎1/‎8 in. tape
Keywords: Judaïsme – Djerba

Djerba (doc 4) - Adler, Israel (1994)
‎1 cassette Digital Audio Tape : digital. stéréo ; ‎3 ‎7/‎8 x ‎2 ‎1/‎2 in., ‎1/‎8 in. tape
Keywords: Judaïsme – Djerba

Djerba doc 2 - Adler, Israel (1994)
‎1 cassette Digital Audio Tape : digital. stéréo ; ‎3 ‎7/‎8 x ‎2 ‎1/‎2 in., ‎1/‎8 in. tape
Keywords: Judaïsme – Djerba

Djerba 94 (2) - Adler, Israel (1994)
‎1 cassette Digital Audio Tape : digital. stéréo ; ‎3 ‎7/‎8 x ‎2 ‎1/‎2 in., ‎1/‎8 in. tape
Keywords: Judaïsme – Djerba

Djerba 94 (1) - Adler, Israel (1994)
‎1 cassette Digital Audio Tape : digital. stéréo ; ‎3 ‎7/‎8 x ‎2 ‎1/‎2 in., ‎1/‎8 in. tape
Keywords: Judaïsme – Djerba

Enregistrement d'un office de l'après midi -Roch `hodech Chevat selon le rite de la communauté de Djerba - Adler, Israel; Roten, Hervé (Ohr Torah, 1994)
1. Brève présentation 2. Introduction-Psaume- texte des sacrifices et kétoreth (Minha) 3. Introduction-Psaume- texte des sacrifices et kétoreth (Minha) 4. Psaume CXLV (Minha) 5. Kadich (Minha) 6. Répétition de la Amida (Minha) 7. Kadich (Minha) 8. Psaume et kadich Psaume LXVII (Minha) 9. Alénou (Minha) 10. Intermède 11. Bénédiction 12. Entretien avec Mr Shmouel Houry
‎1 cassette audio : analog., ‎1 ‎7/‎8 ips ; ‎3 ‎7/‎8 x ‎2 ‎1/‎2 in., ‎1/‎8 in. tape
Keywords: Judaïsme – Djerba

Djerba 4 (Doc 1) - Adler, Israel (1994)
‎1 cassette Digital Audio Tape : digital. stéréo ; ‎3 ‎7/‎8 x ‎2 ‎1/‎2 in., ‎1/‎8 in. tape
Keywords: Judaïsme – Djerba

Djerba 3 - Adler, Israel (1994)
‎1 cassette Digital Audio Tape : digital. stéréo ; ‎3 ‎7/‎8 x ‎2 ‎1/‎2 in., ‎1/‎8 in. tape
Keywords: Judaïsme – Djerba

La communauté juive de Djerba ; secrets d’une pérennité - Qabla, Gabriel (Confluences Méditerranée, 1994)
Keywords: Judaïsme – Djerba

La Ghriba de Djerba: Promesse d’un autre avenir ? - Freund, Wolfgang Slim (Réalités, 1994)
Keywords: Judaïsme – Djerba

Le Pèlerinage de la Ghriba à Djerba - Umm Hnina, Taïta; Rosenthal, Régine; Trabelsi, Victor (Victor Trabelsi, 1994)
Keywords: Judaïsme – Djerba

Jerba and Tripoli: A Comparative Analysis of Two Jewish Communities in the Maghrib - Goldberg, Harvey E. (Journal of Mediterranean Studies, 1994)
Responses to modernity in two North African Jewish centres—Jerba in southern Tunisia and Tripoli in Libya—are compared. The paper first demonstrates the close cultural connections between these communities during the past several centuries. It then shows how Jerba developed as the more active community, in terms of rabbinic culture, in the late 19th century. Next, it points to the main directions the two communities took in response to contact with Europe in the 19th and 20th centuries—sustained resistance on the part of the Jews of Jerba and pragmatic accommodation, while maintaining attachment to tradition, on the part of the Jews of Tripoli. Particular attention will be paid to the way rabbinic culture interacted with wider communal religious culture in each instance. Finally, various explanations for this difference are considered, while citing comparative material from Tunisia and Tripolitania.
Keywords: Judaïsme – Djebel Nefousa; Judaïsme – Djerba